Negative electrode material, preparation method thereof, negative electrode sheet and lithium ion battery

CN121237867BActive Publication Date: 2026-09-18BTR NEW MATERIAL GRP CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410868689.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-28
Publication Date
2026-09-18
Estimated Expiration
2044-06-28

AI Technical Summary

Technical Problem

但是锂掺杂后,会改变原硅氧材料的结构,带来其他性能上的问题

Benefits of technology

本申请负极材料使用第一ICP测试方案和第二ICP测试方案分别测得的锂含量之比I1/I2反映了负极材料中的锂被硅和硅氧化物包裹的程度以及锂在负极材料中分散的均匀程度,通过将I1/I2控制在0.5≤I1/I2≤0.9,负极材料中的锂能够均匀掺杂于硅氧材料中,不会导致硅晶粒增长过大而聚集,减少了负极材料的阻抗变大、满电膨胀变大以及电池循环性能变差,且能够减少负极材料中的锂大部分掺杂在负极材料表层,能够减少锂在调浆过程水解到浆料中而导致浆料产气,从而改善了电池的阻抗、膨胀和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121237867B_ABST
    Figure CN121237867B_ABST
Patent Text Reader

Abstract

This application provides an anode material and its preparation method, an anode electrode sheet, and a lithium-ion battery. The anode material includes a silicon-based core and a coating layer that at least partially covers the surface of the silicon-based core. The silicon-based core comprises lithium silicate and silicon. In a first ICP test scheme, after digesting a specified amount of the anode material with a mixture of hydrochloric acid and nitric acid, the lithium content in the anode material is measured to be I1 using an ICP spectrometer. In a second ICP test scheme, after digesting the specified amount of the anode material with a mixture of hydrofluoric acid and HNO3, the lithium content in the anode material is measured to be I2 using an ICP spectrometer. Then, I1 / I2 satisfies 0.5≤I1 / I2≤0.9. In this application, the I1 / I2 ratio in the anode material reflects the degree to which lithium is encapsulated by silicon and silicon oxide in the anode material, as well as the uniformity of lithium dispersion in the anode material. By controlling I1 / I2 to 0.5≤I1 / I2≤0.9, it is possible to reduce the hydrolysis of lithium into the slurry during the slurry preparation process, which would lead to gas generation in the slurry and improve the battery's impedance, expansion, and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a negative electrode material and its preparation method, a negative electrode sheet and a lithium-ion battery. Background Technology

[0002] As the application of lithium-ion batteries continues to expand and deepen, the performance requirements for lithium-ion batteries are also becoming increasingly stringent, especially in terms of energy density. Traditional graphite anode materials are no longer sufficient to meet the growing market demand. As a high-specific-capacity anode material, silicon-oxygen materials have attracted much attention in recent years. Silicon-oxygen anode materials have a specific capacity exceeding 2000 mAh / g, but their relatively lower initial coulombic efficiency, poorer conductivity, and inferior cycle and rate performance compared to graphite materials limit their practical applications.

[0003] To improve the performance of silicon-oxygen materials, enterprises, universities, and other related institutions have developed many methods. Lithium doping can significantly improve the initial coulombic efficiency of silicon-oxygen materials. However, lithium doping alters the original structure of the silicon-oxygen material, leading to other performance problems. For example, uneven lithium doping can cause gas generation in aqueous slurries, making the material unprocessable, and can also cause excessive silicon grain growth, ultimately resulting in high battery impedance, large anode volume expansion, and rapid battery cycle degradation. Therefore, developing an anode material that balances high capacity and initial efficiency with low impedance and low expansion is essential. Summary of the Invention

[0004] This application provides an anode material and its preparation method, an anode electrode sheet, and a lithium-ion battery. By oxidizing the carbon material coated on the surface of the silicon-based core, lithium in the anode material can be uniformly doped into the silicon-oxygen material, which will not cause excessive growth and aggregation of silicon grains. This can reduce the increase in impedance of the anode material, the increase in full-charge expansion, and the deterioration of battery cycle performance. In addition, it can reduce the amount of lithium doped on the surface of the anode material, and reduce the amount of lithium hydrolyzed into the slurry during the slurry preparation process, which would lead to gas generation in the slurry.

[0005] The technical solution of this application is as follows: In a first aspect, this application provides a negative electrode material, comprising a silicon-based core and a coating layer that at least partially covers the surface of the silicon-based core. The silicon-based core comprises silicon and lithium silicate. After digesting the negative electrode material with a mixture of hydrochloric acid and nitric acid in the first ICP test scheme, the lithium content in the negative electrode material was measured to be I1 using an ICP spectrometer. In the second ICP testing protocol, after digesting the negative electrode material with a mixture of hydrofluoric acid and HNO3, the lithium content in the negative electrode material was determined to be I2 using an ICP spectrometer. Then I1 / I2 satisfies 0.5≤I1 / I2≤0.9.

[0006] Secondly, this application also provides a method for preparing the negative electrode material described in the first aspect, comprising the following steps: Silicon-oxygen raw materials are mixed with carbon sources and then carbon-coated to obtain carbon-coated silicon-oxygen powder. An oxidant solution is prepared and a surfactant is added. The carbon-coated silicon oxide powder is then immersed in the oxidant solution for surface oxidation. The surface-oxidized silicon-oxygen powder is mixed with a lithium source and then subjected to heat treatment to obtain a negative electrode material.

[0007] Thirdly, this application provides a negative electrode sheet, comprising the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.

[0008] Fourthly, this application provides a lithium-ion battery, including the negative electrode sheet described in the third aspect.

[0009] The beneficial effects of this application are: The ratio I1 / I2 of the lithium content measured by the first ICP test scheme and the second ICP test scheme of this application reflects the degree to which lithium in the negative electrode material is wrapped by silicon and silicon oxide and the uniformity of lithium dispersion in the negative electrode material. By controlling I1 / I2 to 0.5≤I1 / I2≤0.9, lithium in the negative electrode material can be uniformly doped in the silicon oxide material, which will not cause excessive growth of silicon grains and aggregation. This reduces the increase in impedance of the negative electrode material, the increase in full-charge expansion and the deterioration of battery cycle performance. It can also reduce the amount of lithium doped on the surface of the negative electrode material, and reduce the amount of lithium hydrolyzed into the slurry during the slurry preparation process, which would lead to gas generation in the slurry. This improves the impedance, expansion and cycle performance of the battery.

[0010] In the preparation method of the negative electrode material of this application, oxidants such as nitric acid or hydrogen peroxide are used to oxidize the surface of the carbon-coated silicon-oxygen raw material, forming a complete and uniform surface oxide layer. Some oxygen-containing groups are formed on the surface of the carbon layer. During lithium doping, these oxygen-containing groups combine with lithium, slowing down the lithium doping reaction and forming a lithium transport layer. This allows lithium to enter the particle interior more uniformly for the lithium doping reaction. Ultimately, the lithium doping reaction is neither too fast, causing excessive heat and silicon aggregation, nor does it result in lithium doping only reacting on the particle surface. Therefore, lithium in the negative electrode material can be uniformly doped into the silicon-oxygen material without causing excessive silicon grain growth and aggregation, thereby improving the battery's impedance, expansion, and cycle performance.

[0011] The lithium-ion battery of this application uses the aforementioned negative electrode sheet, resulting in high battery capacity and initial coulombic efficiency, low electrode resistivity, high cycle capacity retention, and low cycle expansion rate. Attached Figure Description

[0012] Figure 1 This is a scanning electron microscope image of the negative electrode material provided in the first aspect of this application.

[0013] Figure 2 This is a flowchart of the method for preparing the negative electrode material provided in the second aspect of this application. Detailed Implementation

[0014] As used in this article: "Prepared from" is synonymous with "comprising". The terms "comprising", "including", "having", "containing", or any other variations thereof as used herein are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements, but may include other elements not expressly listed or elements inherent to such a composition, step, method, article, or apparatus. The conjunction "composed of" excludes any unnamed elements, steps, or components.

[0015] When a quantity, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range “1–5” is disclosed, the described range should be interpreted as including ranges “1–4”, “1–3”, “1–2”, “1–2 and 4–5”, “1–3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range is intended to include its endpoints and all integers and fractions within that range.

[0016] In these embodiments, unless otherwise specified, the portions and percentages are all by weight.

[0017] "Parts by mass" refers to the basic unit of measurement that expresses the mass ratio of multiple components. One part can represent any unit mass, such as 1g or 2.689g. If we say that component A has "a" parts by mass and component B has "b" parts by mass, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it can mean that the mass of component A is aK and the mass of component B is bK (where K is any number representing a multiplier). It is important to understand that, unlike parts by mass, the sum of the mass parts of all components is not limited to 100 parts.

[0018] "And / or" is used to indicate that one or both of the described situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0019] The first aspect of this application provides a negative electrode material, the scanning electron microscope image of which is shown below. Figure 1 As shown. The anode material comprises a silicon-based core and a coating layer that at least partially covers the surface of the silicon-based core, wherein the silicon-based core contains lithium silicate and silicon.

[0020] It should be noted that in the existing technology, during the preparation of the negative electrode material, the silicon-oxygen raw material (SiO2) y In the region (0 < y ≤ 2), silicon dioxide and silicon in a sub-oxidized state exist. After pre-lithiation of the silicon-oxygen raw material to form a silicon-based core, the active oxygen in the silicon-oxygen raw material reacts with exogenous lithium to form lithium-containing silicates, such as at least one of Li₂SiO₃, Li₂Si₂O₅, and Li₄SiO₄. Lithium silicate can alleviate the consumption of active lithium during the formation of the SEI (Solid Electrolyte Interphase) film in lithium-ion batteries, thereby improving the initial efficiency of the anode material.

[0021] While lithium doping improves the initial efficiency of silicon-oxygen anode materials, it also alters the structure of these materials. For example, uneven lithium doping can cause the anode material to generate gas in aqueous slurry, making it unprocessable. It can also cause excessive growth of silicon grains, resulting in high impedance, large expansion, and poor cycle life in the final battery.

[0022] To alleviate the problem of performance degradation of silicon-oxygen anode materials caused by uneven lithium doping, the anode material provided by the first aspect of this application reduces the excessive encapsulation of lithium elements by silicon or silicon oxide, reduces the amount of lithium compounds doped on the surface of the anode material, thereby reducing the impedance and expansion of the anode material and improving the cycle performance of the battery.

[0023] Based on the above considerations, in order to improve the initial efficiency, impedance, and cycle performance of silicon-oxygen system batteries, the lithium content of the negative electrode material in this application meets the following conditions: If the lithium content of the negative electrode material is tested using the first ICP testing method and is I1 (in ppm), and the lithium content of the material is tested using the second ICP testing method and is I2 (in ppm), then I1 / I2 satisfies 0.5 ≤ I1 / I2 ≤ 0.9. Specifically, it can be 0.5, 0.6, 0.7, 0.8, 0.9, or any value within the range of any two of the above values.

[0024] It is understandable that the first ICP testing method uses a mixture of HCl and HNO3 (i.e., aqua regia) to digest the negative electrode material. Because this solution cannot dissolve silicon and silicon oxides, if some lithium is protected by silicon and silicon oxides, that portion of lithium is difficult to dissolve and detect. The second ICP testing method uses a mixture of HF (hydrofluoric acid) and HNO3 to digest the negative electrode material. This solution can dissolve silicon and silicon oxides; therefore, even if some lithium is protected by silicon or silicon oxides, the total lithium content in the negative electrode material can still be detected. Therefore, by comparing the lithium content detected by the two methods, the distribution of lithium can be understood. In the negative electrode material provided in this application, if I1 / I2 < 0.5, it indicates that a significant amount of lithium (content of I2-I1) in the negative electrode material is coated by silicon and silicon oxide, resulting in a lower lithium content I1 detected by the first ICP test scheme. This means that excessive lithium (content of I2-I1) is protected by silicon and silicon oxide and is not detected. It is speculated that during the pre-lithiation process, silicon aggregates and encapsulates the lithium-containing compounds. This can be understood as follows: lithium content of I2-I1 is too sparsely distributed in the silicon-based core and is encapsulated by silicon and silicon oxide, thus preventing detection by the first ICP test scheme. Conversely, a sparse distribution of lithium in the silicon-based core implies that the silicon distribution is aggregated. This aggregation of silicon leads to increased material impedance, greater full-charge expansion, and easier pulverization during cycling, resulting in poor battery cycle performance.

[0025] If I1 / I2 > 0.9, it indicates that very little lithium is coated with silicon or silicon oxide in the negative electrode material. This is presumably because during the pre-lithiation process, most of the lithium doping is concentrated on the surface of the negative electrode material particles and does not uniformly penetrate into the interior of the particles. Most of the lithium hydrolyzes into the slurry during the slurry preparation process, leading to gas generation, unstable sedimentation, and other problems. Even when the negative electrode material is made into a battery, gas generation during storage remains a significant issue.

[0026] Therefore, since the lithium content of the anode material in this application satisfies 0.5≤I1 / I2≤0.9, the lithium distribution in the anode material does not exhibit excessive sparse distribution of lithium in the silicon-based core, nor does it show lithium concentration on the surface of the anode material particles. It can be uniformly doped into the silicon-oxygen material without causing excessive silicon grain growth and aggregation (see...). Figure 1This reduces the increase in impedance, full-charge expansion, and deterioration of battery cycle performance of the negative electrode material. Furthermore, it reduces the amount of lithium doped onto the surface of the negative electrode material, minimizing lithium hydrolysis into the slurry during the slurry preparation process and thus reducing gas generation. This improves the battery's impedance, expansion, and cycle performance. In some embodiments, the lithium content I1 measured in the first ICP test scheme ranges from 2.5 wt% to 10 wt%, and the lithium content I2 measured in the second ICP test scheme ranges from 5 wt% to 12 wt%. It is understood that selecting I1 and I2 within these ranges is beneficial for improving the initial efficiency and capacity of the negative electrode material, and thus for improving the battery's cycle performance.

[0027] In some embodiments, lithium silicate includes at least one of Li2SiO3 and Li2Si2O5.

[0028] In some embodiments, the silicon-based core comprises silicon oxide with the general chemical formula SiO. x , where 0 < x ≤ 2, and x can take the values ​​of 0.1, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 1.95, 2 or any value between them.

[0029] In some embodiments, the silicon-based core comprises silicon oxide, which comprises silicon and oxygen elements, wherein the atomic ratio of silicon to oxygen is 0 to 2, excluding 0, and the atomic ratio may be 0.1, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 1.95, 2 or any value therebetween.

[0030] In some embodiments, the silicon comprises silicon grains with a size ≤15nm. The average size of the silicon grains can specifically be 15nm, 14nm, 13nm, 12nm, 10nm, 8nm, 7.5nm, 7nm, 6nm, 5nm, 3nm, 2nm, 1nm, etc., and is not limited thereto. Preferably, the silicon grain size is ≤10nm. Understandably, when the average size of the silicon grains is too large, the expansion stress generated during lithium intercalation is uneven, which can easily lead to the breakage of the anode material particles, loss of electrochemical activity, and consequently reduced product cycle performance. Therefore, controlling the average size of the silicon grains within the above range is beneficial for improving the uniformity of expansion stress in the anode material particles, reducing particle breakage, and enabling the anode material to achieve an ideal balance in cycle performance, capacity utilization, and rate performance, thus obtaining optimal overall performance.

[0031] In some embodiments, the mass content of lithium silicate in the negative electrode material is 30% to 80%, specifically 30%, 40%, 50%, 55%, 60%, 70%, 75%, or 80%, or other values ​​within the above range. Understandably, if the lithium silicate content is too low, it indicates that the material has too low a lithium content and low first-efficiency; if the lithium silicate content is too high, it indicates that the material has too high a lithium content and low capacity.

[0032] In some embodiments, the lithium content in the negative electrode material is 0.1wt% to 20wt%, specifically 0.1wt%, 0.5wt%, 1wt%, 2%, 5wt%, 10wt%, 15wt%, or 20wt%, or other values ​​within the above range.

[0033] In some implementations, the overall lithium to oxygen mass ratio of the negative electrode material is x, and the lithium to oxygen mass ratio in the surface layer of the negative electrode material is y. The relationship between x and y satisfies y / x ≥ 0.4. If y / x < 0.4, it indicates that too much lithium in the negative electrode material is protected by silicon and silicon oxide and is not detected. Excessive lithium protection may be due to the aggregation of silicon or silicon oxide within the particles, trapping more lithium within the aggregates. The aggregation of silicon and silicon oxide is detrimental to lithium-ion conduction and material expansion, presumably due to insufficient uniformity of lithium distribution during the pre-lithiation process. Ultimately, this can lead to increased impedance of the material and poorer battery cycle performance.

[0034] In some embodiments, the negative electrode material further includes a coating layer located on at least a portion of the surface of the silicon-based core (silicon and / or silicon-oxygen materials, etc.), the coating layer containing carbon material, wherein the mass content of carbon element in the negative electrode material is 1% to 10%, specifically 1%, 2%, 3%, 5%, 6%, 7%, 8%, 9%, or 10%, etc., and of course, other values ​​within the above range are also possible, without limitation. Understandably, within the carbon content range of this application, the material exhibits high conductivity, fewer surface side reactions, high initial capacity, and low impedance.

[0035] In some embodiments, the pH of the negative electrode material is 10 to 12, specifically 10, 10.5, 11, 11.5 or 12, etc., which are not limited here.

[0036] In some implementations, the specific surface area of ​​the negative electrode material is 0.1 m². 2 / g ~5m 2 / g, specifically 0.1m 2 / g, 1.0 m 2 / g, 1.5 m 2 / g, 1.8 m 2 / g, 2.0 m 2 / g, 2.5 m 2 / g、3.0 m 2 / g、3.6 m 2 / g, 4.0 m 2 / g or 5 m 2 / g, but not limited to the listed values; other unlisted values ​​within this range also apply. Understandably, a smaller specific surface area is better. An excessively large specific surface area can easily lead to the formation of an SEI film, consuming too much irreversible lithium salt and reducing the battery's initial efficiency.

[0037] In some embodiments, the moisture content of the negative electrode material is 0.01~0.5%wt, specifically 0.01wt, 0.02wt, 0.1wt, 0.2wt or 0.5wt, etc., which are not limited here.

[0038] In some embodiments, the oxygen content in the negative electrode material is 20% to 40% by mass, specifically 20%, 25%, 30%, 35% or 40%, etc., which is not limited here.

[0039] A second aspect of this application also provides a method for preparing the above-mentioned negative electrode material, which includes the following steps: Step S1: Take silicon-oxygen raw materials and perform carbon coating.

[0040] Silicon-oxygen raw materials are mixed with carbon sources and carbonized to achieve carbon coating, resulting in carbon-coated silicon-oxygen powder.

[0041] In some embodiments, the general chemical formula of the silicon-oxygen raw material is SiO. y , where 0 < y ≤ 2, for example, y can be 0.1, 0.5, 0.8, 1, 1.5, 1.8, 2 or any value within the range of any two of the above values.

[0042] It is understood that the silicon-oxygen raw material can be purchased commercially or produced by reacting Si and SiO2 raw materials; no limitation is made here.

[0043] In some embodiments, the carbon source includes a gaseous carbon source and a solid carbon source. The gaseous carbon source includes at least one selected from alkanes, cycloalkanes, alkenes, alkynes, and aromatic hydrocarbons. The solid carbon source includes at least one selected from sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride, and asphalt.

[0044] The carbonization temperature is 600℃~1000℃, and the carbonization time is 0.5h~10h. Different carbon sources require different temperatures and carbonization times.

[0045] Step S2 involves surface oxidation treatment of the carbon-coated silicon oxide powder.

[0046] The carbon-coated silicon oxide powder is surface-oxidized using oxidants such as nitric acid or hydrogen peroxide, and surfactants (e.g., sodium dodecyl sulfate, sodium dodecylaminopropionate, stearic acid, dodecyl ethoxysulfonate, octadecyl dihydroxyethylamine oxide) are added to promote the dispersion of silicon oxide powder in the solution and improve the oxidation uniformity. The concentration of the oxidant is 0.1~2 mol / L, and the oxidation time is 6-12 h.

[0047] The role of surface oxidation: Some oxygen-containing groups are formed on the surface of the carbon layer. During the lithium doping process, the oxygen-containing groups will combine with lithium. On the one hand, it slows down the lithium doping reaction, and on the other hand, it forms a lithium transport layer, so that lithium can enter the particle interior more evenly for lithium doping reaction. In the end, it will not cause silicon to aggregate due to excessively fast lithium doping reaction and severe exothermic reaction, nor will it cause lithium doping to react only on the particle surface.

[0048] If the concentration of the oxidant is too low, a complete and uniform surface oxide layer cannot be formed, which cannot effectively improve the lithium doping reaction. The silicon grains in the material are large, and the slurry is also prone to gas generation. If the concentration of the oxidant is too high, the material is easily over-oxidized, resulting in a lower specific capacity and first-stage efficiency of the anode material.

[0049] Different oxidant concentrations require different oxidation times.

[0050] Step S3: The silicon-oxygen powder material after surface oxidation treatment is mixed with lithium source and heat-treated, and then screened to obtain the negative electrode material.

[0051] The lithium source includes at least one of lithium metal, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride, and lithium aluminum hydride.

[0052] The temperature of the above heat treatment is 400℃~900℃, and the heat treatment time is 4h~12h.

[0053] The screening method includes at least one of the following: fixed screen, drum screen, resonant screen, roller screen, vibrating screen, and chain screen, and the screening mesh is ≥200 mesh.

[0054] Furthermore, a third aspect of this application provides a negative electrode sheet, comprising a negative electrode material prepared using the negative electrode material provided in the above embodiments of the present invention or a negative electrode material prepared using the preparation method of the negative electrode material provided in the above embodiments of the present invention.

[0055] Furthermore, a fourth aspect of this application provides a lithium-ion battery, including a positive electrode, the aforementioned negative electrode, an electrolyte, and a separator located between the positive electrode and the negative electrode.

[0056] The implementation schemes of this application will be described in detail below with reference to specific embodiments. However, those skilled in the art will understand that the following embodiments are only for illustrating this application and should not be regarded as limiting the scope of this application. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0057] Example 1 This embodiment provides a negative electrode material for lithium-ion batteries, and its preparation method includes: Step (1) Take 2 kg of SiO powder, place it in a tube furnace and heat it to 900°C under nitrogen protection. Then introduce acetylene, keep it at the temperature for 3 hours and then cool it to obtain carbon-coated SiO material. Step (2) Prepare 3000ml of nitric acid solution with a concentration of 1mol / L in a plastic beaker, add 2g of sodium dodecyl sulfate, add the carbon-coated SiO material from step (1) into the nitric acid solution, stir and react for 8 hours, and filter to obtain powder material; Step (3) Take 100g of LiH and 1kg of the powder material obtained in step (2) and mix them. Then place them in a box furnace under nitrogen protection, heat them to 750℃, keep them at the temperature for 5 hours, and then take them out and sieve them to obtain the negative electrode material.

[0058] Example 2 The preparation method of the negative electrode material provided in this embodiment is the same as that in embodiment 1, except that: in step (2), 3000 ml of hydrogen peroxide solution with a concentration of 1 mol / L is prepared in a plastic beaker, and 2 g of sodium dodecyl sulfate is added. Then, the carbon-coated SiO material in step (1) is added to the hydrogen peroxide solution, stirred and reacted for 10 hours, filtered to obtain powder material, and dried at 100°C for 24 hours.

[0059] Example 3 The preparation method of the negative electrode material provided in this embodiment is the same as that in embodiment 1, except that: in step (2), 3000 ml of 0.1 mol / L nitric acid solution is prepared in a plastic beaker, and 2 g of sodium dodecyl sulfate is added. The carbon-coated SiO material in step (1) is added to the nitric acid solution, stirred and reacted for 12 hours, filtered to obtain powder material, and dried at 100°C for 24 hours.

[0060] Example 4 The preparation method of the negative electrode material provided in this embodiment is the same as that in embodiment 3, except that the concentration of the nitric acid solution in step (2) is changed from 0.1 mol / L to 2.0 mol / L, and the stirring reaction time is changed from 12 hours to 6 hours.

[0061] Example 5 The preparation method of the negative electrode material provided in this embodiment is the same as that in embodiment 3, except that the concentration of the nitric acid solution in step (2) is changed from 0.1 mol / L to 0.05 mol / L.

[0062] Example 6 The preparation method of the negative electrode material provided in this embodiment is the same as that in embodiment 3, except that the concentration of the nitric acid solution in step (2) is changed from 0.1 mol / L to 2.2 mol / L, and the stirring reaction time is changed from 12 hours to 6 hours.

[0063] Comparative Example 1 This comparative example provides a negative electrode material for lithium-ion batteries, the preparation method of which includes: Step (1) Take 2 kg of SiO powder, place it in a tube furnace and heat it to 900°C under nitrogen protection. Then introduce acetylene, keep it at the temperature for 3 hours and then cool it to obtain carbon-coated SiO material. Step (2) Take 100g LiH and 1kg of carbon-coated SiO material obtained in step 1 and mix them. Then place them in a box furnace under nitrogen protection, heat to 750℃, keep warm for 5h, take them out and sieve them to obtain the negative electrode material.

[0064] Comparative Example 2 This comparative example provides a negative electrode material for lithium-ion batteries, the preparation method of which includes: Step (1) Take 2 kg of SiO powder, place it in a tube furnace and heat it to 900°C under nitrogen protection. Then introduce acetylene, keep it at the temperature for 3 hours and then cool it to obtain carbon-coated SiO material. Step (2) Take 100g LiH and 1kg of carbon-coated SiO material obtained in step 1 and mix them. Then place them in a box furnace under nitrogen protection, heat to 850℃, keep warm for 5h, take them out and sieve them to obtain the negative electrode material.

[0065] Performance testing methods: I. The Li content in the material was determined using the ICP method.

[0066] ① First ICP test protocol: 0.500g of negative electrode material was placed in a clean platinum crucible and then calcined in a muffle furnace under air atmosphere at 750℃ for 2 hours to completely remove carbon. The cooled calcination residue was taken together with 8ml of aqua regia and a certain amount of ultrapure water and digested in a graphite digester at 130℃ for 30min. The digested solution was then diluted to 100mL in a plastic volumetric flask. Finally, the Li content of the material was tested using an ICP spectrometer (Agilent 5800VDV ICP-OES).

[0067] ② Second ICP test procedure: 0.500g of negative electrode material was placed in a clean platinum crucible and then calcined in a muffle furnace under air atmosphere at 750℃ for 2 hours to completely remove carbon. The cooled residue was then reacted with a mixed acid of 4mL HNO3 and 6mL HF. The platinum crucible containing the solution was then placed on a 350℃ hot plate until the solvent was completely evaporated. After the crucible cooled, 6mL HCl was added and heated until the residue was completely dissolved. The solution was then taken and diluted to a 100mL plastic volumetric flask. Finally, the Li content of the material was tested using an ICP spectrometer (Agilent 5800VDV ICP-OES).

[0068] 2. XRD was measured using a Panaco X'pert PRO X-ray diffractometer within a scanning range of 9.749°–41.157°. Scan step size: 0.013°, scan speed: 6.060° / min, voltage: 40kV, current: 40mA. The file was opened with Jade 6, background removed and smoothed, and the Si peaks in the 26°–30° range were fitted. The Scherrer equation was used: D = kλ / βcosθ, where d is the average grain size perpendicular to the Si reflective crystal plane (111), β (radians) is the broadening degree of the half-maximum width at half maximum (FWHM) of this crystal plane = FWHM * π / 180. K is the Scherrer constant, taken as 0.89; θ is the diffraction angle; λ is the incident X-ray wavelength, 0.15406 nm. Full width at half maximum (FWHM) is the maximum width at half maximum. Half-width at half maximum (FHWM), also known as half-peak width, half-peak region width, or region half-width, is a chromatographic term referring to the peak width at half the peak height. It is calculated by drawing a straight line parallel to the base of the peak through the midpoint of the peak height, and finding the distance between the two points where this line intersects the peak. Both FHWM and θ can be obtained using XRD.

[0069] Si crystallite size: XRD peaks were measured using a Panaco X'pert Pro X-ray diffractometer, and then the Si peaks in the XRD were fitted and analyzed using X'pert High Score software to calculate the Si crystallite size.

[0070] Software usage instructions and parameter settings: 1. Open the X'pert High Score software, click Open, locate the file you just saved, and click OK to open the file; 2. Remove Ka2: Right-click on a blank area of ​​the spectrum and click "Strip K-Alpha2", or select "Treatment" - "Strip K-Alpha2" in the toolbar, click "Strip K-Alpha2" in the pop-up dialog box, and then click "Replace"; 3. Smoothing: Right-click on a blank area of ​​the spectrum, click "Smooth" in the menu, click "Smooth" in the pop-up dialog box, and then click "Replace"; select Quintic mode; 4. Define the background: Right-click on a blank area of ​​the spectrum, click "Determine Background", click "Background" in the pop-up dialog box, and then click "Accept"; select 20 for Guanularity and 5 for blending factor; 5. Peak Search: Right-click on a blank area of ​​the spectrum peak, click "Search Peaks", and select the peak search parameters in the pop-up dialog box: Minimum significance: 2.0 Minimum tip width: 0.1 Maximum tip width: 5 Peak base width: 10. Click "Search Peaks" in the dialog box shown on the right above, and then click "Accept". 6. Peak Fitting: Right-click on a blank area of ​​the spectrum, click "Set Manual Ranges", enter the angle range "26~30" in the pop-up dialog box, and then click "OK"; then right-click on a blank area of ​​the spectrum again, click "Fit Profile", and repeat this process several times until the peak data in the "peak list" on the right no longer changes. Record the angle (θ), full width at half maximum (FWHM), and peak height of the peaks within the range of approximately 28.4°.

[0071] III. Electrical Performance Testing: Electrochemical performance testing (1) First Coulomb efficiency test: a. Preparation of lithium-ion batteries: The composite materials prepared in the above examples and comparative examples are used as negative electrode active materials. The conductive carbon black and CMC / SBR are mixed evenly at a mass ratio of 75:15:10 and coated on copper foil to prepare a negative electrode sheet. A lithium metal sheet is used as a positive electrode sheet and PP / PE is used as a separator to make a button battery.

[0072] b. The battery was tested using a Landon Newway 5V / 10mA battery tester. The voltage was 1.5V and the current was 0.1C. The initial coulombic efficiency was calculated as the initial charge specific capacity / the initial discharge specific capacity.

[0073] (2) Cyclic performance test: a. Preparation of lithium-ion batteries: The composite materials prepared in the above examples and comparative examples are mixed with graphite at a mass ratio of 15:85 to obtain negative electrode active materials. Then, the negative electrode active materials, conductive carbon black, CMC and SBR are mixed evenly at a mass ratio of 92:4:2:2 and coated on copper foil to prepare a negative electrode sheet. The lithium metal sheet is used as the positive electrode sheet, and PP / PE is used as the separator to make a button battery. b. The battery was tested using a Landon Newway 5V / 10mA battery tester. The voltage was 1.5V and the current was 0.1C. The 50-cycle retention rate was calculated as the specific capacity at the 50th discharge cycle / the specific capacity at the first discharge cycle.

[0074] (3) Electrode impedance test: Preparation of lithium-ion batteries: Silicon oxide and graphite were combined to a concentration of 500 mAh / g as the negative electrode active material. The electrode was fabricated using an active material:CMC (MAC350HC):SP:SBR (451B) ratio of 95.3:1.3:1.5:1.9. A 5cm × 5cm square block was taken, and nine points were randomly tested using an electrode resistivity meter (IEST Yuaneng Technology, model: BER2500). The average value was taken as the resistivity of the measured material.

[0075] IV. Calculation of the mass content of lithium and oxygen in anode materials The total oxygen (O) content of the material was tested using an ONH elemental analyzer (ONH-2000). The specific procedure was as follows: 10-13 mg of the active material was weighed, wrapped in nickel foil, and then placed into a graphite crucible within the ONH elemental analyzer for testing. The mass content of lithium (x) was calculated using the above data combined with the lithium content obtained from the second ICP testing method.

[0076] V. Calculation of the mass ratio of lithium to oxygen in the surface layer of the negative electrode material The mass content of Li and O elements on the surface of the material was measured using X-ray photoelectron spectroscopy (ThermoScientific K-Alpha). The excitation source used was AlKα rays with a beam size of 400 μm. The pass energy for the full spectrum scan was 100 eV with a step size of 1 eV. Finally, the mass ratio y of Li and O elements was analyzed using Avantage software.

[0077] VI. Comparison Test Method The specific surface area and pore size analyzer of the American company, TriStar 3000 & 3020, was used to test the specific surface area of ​​powder samples by gas adsorption method (nitrogen adsorption multi-point BET) under low temperature controlled by liquid nitrogen cooling. After measuring the amount of gas adsorbed on the solid surface at different relative pressures under isothermal and low temperature conditions, the monolayer adsorption amount of the sample was calculated based on the Brownnor-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of ​​the material.

[0078] VII. pH Value Testing Method To test the pH value of materials using a Mettler FE20 pH meter, calibration is required before use. Calibration method: Remove the protective sleeve from the electrode, rinse several times with pure water, and soak in distilled water for 30 minutes; remove the electrode, dry it with a paper towel or filter paper, then pour 4.0 L of buffer solution into a clean polyethylene beaker, and press the calibration button to begin calibration; wait for the instrument to stabilize (display will show...) Then, calibrate by sequentially adding buffer solutions of 7.00 and 9.21; after calibration with the three buffer solutions, save the results or recalibrate according to the calibration results.

[0079] Test: Accurately weigh 5.00±0.01g of material powder onto a balance, place it in a 100ml glass beaker, add 30ml of pure water, stir with a glass rod to disperse it completely in the pure water, sonicate in an ultrasonic cleaner for 5 minutes, then remove and let stand. Use a pH tester to measure the pH value of the supernatant and read the value.

[0080] The above-mentioned performance tests were performed on the anode materials prepared in the above embodiments and comparative examples, and the test results are shown in Table 1.

[0081] Table 1. Summary of Performance Test Results According to the test results in Table 1, in Examples 1-4 of this application, after obtaining the carbon-coated SiO material, the surface of the SiO material was oxidized using strong oxidants such as nitric acid or hydrogen peroxide. This resulted in the lithium content ratio I1 / I2 of the negative electrode material, measured by the first ICP test scheme and the second ICP test scheme respectively, being controlled at 0.5≤I1 / I2≤0.9. The lithium-ion batteries with the negative electrode material of Examples 1-4 have higher capacity and first-time efficiency. Compared with the carbon-coated SiO material in Comparative Examples 1-2, which was not surface-oxidized, the slurry of the negative electrode material of Examples 1-4 has better stability, the electrode resistivity of the negative electrode material of Examples 1-4 is lower, and the lithium-ion batteries with the negative electrode material of Examples 1-4 have higher capacity retention and lower cycle expansion rate.

[0082] Although Examples 1 and 2 used different types of oxidants, their concentrations and oxidation times were similar, resulting in similar surface oxidation degrees and thus similar test results. In Example 3, the oxidant concentration (0.1 mol / L) was significantly lower, and the oxidation time was longer, with an I1 / I2 ratio close to 0.9. This indicates that very little lithium in the anode material is protected by silicon or silicon oxide, meaning the silicon aggregation is low, resulting in lower impedance. In Example 5, the anode material prepared using an even lower concentration (0.05 mol / L) of oxidant for surface oxidation of the carbon coating layer had an I1 / I2 ratio greater than 0.9 and a silicon grain size greater than 10 nm. After two days of stable storage, sedimentation and gas production occurred, indicating that the oxidant concentration was too low to form a complete and uniform surface oxide layer, failing to effectively improve the lithium doping reaction. The material also had large silicon grains, and the slurry was prone to gas production. In contrast, Examples 4 and 6 have higher oxidant concentrations, shorter oxidation times, and smaller I1 / I2 ratios, indicating that more lithium in the negative electrode material is protected by silicon or silicon oxide, meaning that the degree of silicon aggregation is higher. Consequently, the impedance is higher, the cycle capacity retention rate is slightly lower, and the cycle expansion rate is slightly higher.

[0083] The negative electrode materials prepared in Comparative Examples 1 and 2, when directly subjected to lithium doping without surface oxidation treatment, exhibited an I1 / I2 ratio greater than 0.9. This indicates that a significant amount of lithium in the negative electrode material is protected by silicon or silicon oxide, meaning that the silicon has a high degree of aggregation. Consequently, the material exhibits high impedance, low cycle capacity retention, and high cycle expansion rate. The silicon grain size in Comparative Example 2 is 15.8 nm, which is larger than 15 nm. The average size of the silicon grains is relatively large, and sedimentation and gas generation occur after one day of stable storage, leading to a decrease in the product's cycle performance.

[0084] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

[0085] Furthermore, those skilled in the art will understand that although some embodiments herein include certain features included in other embodiments but not others, combinations of features from different embodiments are intended to be within the scope of this application and form different embodiments. For example, any of the embodiments claimed above can be used in any combination. The information disclosed in this background section is intended only to enhance the understanding of the general background of this application and should not be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.

Claims

1. A negative electrode material, characterized in that, It includes a silicon-based core and a coating layer that at least partially covers the surface of the silicon-based core. The silicon-based core comprises lithium silicate and silicon. After digesting a specified amount of the negative electrode material using a mixture of hydrochloric acid and nitric acid in the first ICP test protocol, the lithium mass content in the negative electrode material was measured to be I1 using an ICP spectrometer. In the second ICP testing protocol, after digesting the specified amount of the negative electrode material with a mixture of hydrofluoric acid and HNO3, the solution was heated until the solvent was completely evaporated. After cooling, HCl was added, and the mixture was heated until the residue was completely dissolved. The lithium content in the negative electrode material was then determined to be I2 using an ICP spectrometer. Then I1 / I2 satisfies 0.5≤I1 / I2≤0.

9.

2. The negative electrode material as described in claim 1, characterized in that, The negative electrode material satisfies y / x≥0.4, where y is the mass ratio of lithium to oxygen obtained by X-ray photoelectron spectroscopy, and x is the mass ratio of lithium to oxygen in the negative electrode material.

3. The negative electrode material as described in claim 1, characterized in that, At least one of the following conditions must be met: a. 2.5wt%≤I1≤10wt%; b. 5 wt% ≤ I2 ≤ 12 wt%.

4. The negative electrode material as described in claim 1, characterized in that, At least one of the following conditions must be met: a. The silicon comprises silicon grains, the size of which is ≤15nm; b. The lithium silicate includes at least one of Li2SiO3, Li2Si2O5, and Li4SiO4; c. The pH value of the negative electrode material is 10-12; d. The specific surface area of ​​the negative electrode material is 0.1 m². 2 / g ~5m 2 / g; e. The moisture content of the negative electrode material is 0.01~0.5wt%; f. The oxygen content in the negative electrode material is 20% to 40% by mass.

5. The negative electrode material as described in claim 1, characterized in that, The lithium silicate content in the negative electrode material is 30% to 80% by mass. The lithium content in the negative electrode material is 0.1wt% to 20wt%.

6. The negative electrode material as described in claim 1, characterized in that, The coating layer comprises carbon material. The carbon content in the negative electrode material is 1% to 10% by mass.

7. The negative electrode material according to claim 1, characterized in that, The silicon-based core comprises silicon oxide, which includes silicon and oxygen elements, wherein the atomic ratio of silicon to oxygen is 0 to 2, excluding 0.

8. The negative electrode material according to claim 2, characterized in that, The silicon-based core comprises silicon oxide, the general chemical formula of which is SiO. x , where 0 < x ≤ 2.

9. A method for preparing a negative electrode material, which is the method for preparing the negative electrode material according to any one of claims 1 to 8, characterized in that, The preparation method of the negative electrode material includes the following steps: Silicon-oxygen raw materials are mixed with carbon sources and then carbon-coated to obtain carbon-coated silicon-oxygen powder. An oxidant solution is prepared and a surfactant is added. The carbon-coated silicon oxide powder is then immersed in the oxidant solution for surface oxidation. The surface-oxidized silicon-oxygen powder is mixed with a lithium source and then subjected to heat treatment to obtain a negative electrode material.

10. The preparation method according to claim 9, characterized in that, The silicon-oxygen raw material is SiO₂. y , 0 < y ≤ 2.

11. The preparation method according to claim 9, characterized in that, In the step of mixing silicon-oxygen raw materials with a carbon source and performing carbon coating treatment to obtain carbon-coated silicon-oxygen powder, the temperature of the carbon coating treatment is 600℃~1000℃, and the time of the carbon coating treatment is 0.5h~10h. In the step of preparing an oxidant solution and adding a surfactant, and then immersing the carbon-coated silicon oxide powder in the oxidant solution for surface oxidation, the concentration of the oxidant in the oxidant solution is 0.1~2 mol / L, and the oxidation time is 6-12 h. In the step of mixing the surface-oxidized silicon-oxygen powder with a lithium source and performing heat treatment to obtain a negative electrode material, the heat treatment temperature is 400℃~900℃, the heat treatment time is 4h~12h, and the negative electrode material obtained by mixing the surface-oxidized silicon-oxygen powder with a lithium source and performing heat treatment is sieved.

12. The preparation method according to claim 11, characterized in that, The preparation method includes at least one of the following features: (1) The carbon source includes a gaseous carbon source and a solid carbon source. The gaseous carbon source includes at least one of alkanes, alkenes, alkynes and aromatic hydrocarbons. The solid carbon source includes at least one of sucrose, glucose, polyethylene, polyvinyl alcohol, polyethylene glycol, polyaniline, epoxy resin, phenolic resin, furfural resin, acrylic resin, polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl chloride and asphalt. (2) The oxidizing agent includes nitric acid or hydrogen peroxide; (3) The surfactants include sodium dodecyl sulfate, sodium dodecylaminopropionate, stearic acid, dodecyl ethoxysulfonate betaine, and octadecyl dihydroxyethylamine oxide.

13. The preparation method according to claim 11, characterized in that, The preparation method includes at least one of the following features: (1) The lithium source includes at least one of lithium metal, lithium hydride, lithium carbonate, lithium hydroxide, lithium borohydride and lithium aluminum hydride; (2) The screening method includes at least one of fixed screen, drum screen, resonant screen, roller screen, vibrating screen and chain screen, and the mesh number of the screening is ≥200 mesh.

14. A negative electrode sheet, characterized in that, The negative electrode material includes any one of claims 1 to 8 or a negative electrode material prepared by the method of any one of claims 9 to 13.

15. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode as described in claim 14, an electrolyte, and a separator located between the positive and negative electrodes.

Citation Information

Patent Citations

  • Negative electrode active substance, mixed negative electrode active substance material and method for producing negative electrode active substance

    CN109155405A

  • Negative electrode active material, negative electrode for battery and battery

    CN114614000A